Comparison Between Skin Staples and Prolene Sutures for Skin Closure in Caesarean Section Patients - Erum Jahan, Nadia Nawaz, Sumera Mahmood, Saima Shabbir, Rahila Imtiaz, Urvashi Gupta (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of wound infection in skin staples versus prolene sutures for skin closure in patients undergoing caesarean section. Subject and Methods: This study comprises 216 patients that underwent caesarean mode of delivery, which were further divided into 2 groups on the basis skin closure. In Group I skin closure was done with staples and in Group II skin was closed with prolene sutures. Type of C section ( elective or emergency) was recorded. Mean and standard deviation was calculated for age, gestational age and skin closure time. Wound infection was recorded based on the presence of any of the following, purulent drainage, cellulitis, abscess or wound demanding debridement and drainage. Results: The mean age of patient in group I was 28.53±4.27 and in Group II was 29.17±4.29. Skin closure time for staples group was recorded as 2.01.±1.01 minutes and for suture group it was 6.46.±2.19 minutes. In skin staples group 19(17.6%) patients developed wound infection and in sutures group 08(7.40%) females got wound infection within 7th post-operative day. Conclusion: Wound infection is less likely to occur in patients of suture group as compared to staples group